2002
DOI: 10.1074/jbc.m112270200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Nitric Oxide Treatment Confer Tolerance to Glucose Starvation in a 5′-AMP-activated Protein Kinase-dependent Manner

Abstract: Hypoxia is a critical event for higher organisms, and cells and tissues react by increasing the oxygen supply by vasodilatation, angiogenesis, and erythropoiesis and maintaining cellular energy by increasing glycolysis and inhibiting anabolic pathways. Stimulation of glycolysis has been regarded as the main response that increases energy production during hypoxia; however, there is an obvious conflict during ischemia, because both the oxygen and glucose supply are insufficient. In this study, we found that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 25 publications
3
77
0
1
Order By: Relevance
“…They were efficiently expressed (Figure 2b). ARK5 belongs to the AMPK catalytic subunit family (Suzuki et al, 2003a); therefore, we also examined the efficacy of antisense RNA expression vector of AMPK-a1 (AMPK-a1/AS and Esumi et al, 2002;Kato et al, 2002). As shown in Figure 2c, an introduction of AMPK-a1/AS into SW480 cells showed a dramatic To examine whether ARK5 promotes cell survival against Fas-mediated cell death, the effect of ARK5 overexpression was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were efficiently expressed (Figure 2b). ARK5 belongs to the AMPK catalytic subunit family (Suzuki et al, 2003a); therefore, we also examined the efficacy of antisense RNA expression vector of AMPK-a1 (AMPK-a1/AS and Esumi et al, 2002;Kato et al, 2002). As shown in Figure 2c, an introduction of AMPK-a1/AS into SW480 cells showed a dramatic To examine whether ARK5 promotes cell survival against Fas-mediated cell death, the effect of ARK5 overexpression was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Akt which is a serine/threonine protein kinase induces cell survival as a result of phosphorylation and several cell death-associated factors, such as Bad (Datta et al, 1997;Peso et al, 1997), caspase-9 (Cardone et al, 1998) and Forkhead , upon the stimulation of growth factor receptor and integrin-induced cell signaling (Datta et al, 1999;Brazil et al, 2002). Furthermore, we recently demonstrated that members of AMPK catalytic subunit family play a major role in tumor cell survival during nutrient starvation and tumorigenesis (Izuishi et al, 2000;Esumi et al, 2002;Hashimoto et al, 2002;Kato et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Similar constitutive tolerance to nutrient deprivation has been observed in some poorly differentiated cancer cell lines, including pancreatic cancers, in which hypovascularity is commonly observed. 9,10,12) Based on our observations we hypothesized that the cancer cells might have acquired the ability to survive in an extremely adverse microenvironment not only through increased angiogenesis, but also by acquiring tolerance to nutrient starvation, i.e., by austerity. 10) Based on these observations, we developed a screening method for compounds that might provide the basis for an antiausterity strategy and identified kigamicin D, which has a novel structure and exhibits preferential cytotoxicity during nutrient starvation.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore speculated that if some compound could abolish cancer cells' tolerance of nutrient starvation, it might be capable of being used to sensitize cancer cells to this hostile environment, resulting in repression of cancer by a new strategy that we termed "anti-austerity." 12) In this study, through screening over 2000 culture media of actinomycetes, we identified a new compound, kigamicin D, a polycyclic xanthone having sugar moieties and a molecular formula of C 48 H 59 NO 19 , as a candidate for this strategy. The possible mode of action of kigamicin D was also investigated.…”
mentioning
confidence: 99%
“…Tumor cells are continuously exposed to hypoxia and glucose starvation because the tumor's demand for their growth always exceeds the supply (Esumi et al 2002). In normal tissues, such as liver parenchyma, a relationship between binucleated cells and cell survival was reported (Morizur et al 2010).…”
Section: Discussionmentioning
confidence: 99%